Interferon-γ–Mediated Allograft Rejection Exacerbates Cardiovascular Disease of Hyperlipidemic Murine Transplant Recipients. Issue 11 (6th November 2015) - Zhou, Jing; Qin, Lingfeng; Yi, Tai; Ali, Rahmat; Li, Qingle; Jiao, Yang; Li, Guangxin; Tobiasova, Zuzana; Huang, Yan; Zhang, Jiasheng; Yun, James J.; Sadeghi, Mehran M.; et al.
Abstract : Rationale: : Transplantation, the most effective therapy for end-stage organ failure, is markedly limited by early-onset cardiovascular disease (CVD) and premature death of the host. The mechanistic basis of this increased CVD is not fully explained by known risk factors. Objective: : To investigate the role of alloimmune responses in promoting CVD of organ transplant recipients. Methods and Results: : We established an animal model of graft-exacerbated host CVD by combining murine models of atherosclerosis (apolipoprotein E–deficient recipients on standard diet) and of intra-abdominal graft rejection (heterotopic cardiac transplantation without immunosuppression). CVD was absent in normolipidemic hosts receiving allogeneic grafts and varied in severity among hyperlipidemic grafted hosts according to recipient–donor genetic disparities, most strikingly across an isolated major histocompatibility complex class II antigen barrier. Host disease manifested as increased atherosclerosis of the aorta that also involved the native coronary arteries and new findings of decreased cardiac contractility, ventricular dilatation, and diminished aortic compliance. Exacerbated CVD was accompanied by greater levels of circulating cytokines, especially interferon-γ and other Th1-type cytokines, and showed both systemic and intralesional activation of leukocytes, particularly T-helper cells. Serological neutralization of interferon-γ after allotransplantation prevented graft-related atherosclerosis, cardiomyopathy, and aortic stiffening in the host. Conclusions: : Our study reveals that sustained activation of the immune system because of chronic allorecognition exacerbates the atherogenic diathesis of hyperlipidemia and results in de novo cardiovascular dysfunction in organ transplant recipients. Abstract : Supplemental Digital Content is available in the text.